TEST OF ANTI-INFLAMATION ACTIVITIES OF PEPAYA LEAF (Carica papaya L.) EXTRACT ON MALE WISTAR RATS INDUCED BY CARAGENAN 1% - Fenny Hasanah; Nurul Hidayah (Jurnal Natural, 2019)
Inflammation is a normal protective response to tissue injuries caused by physical trauma, destructive chemicals, or microbiological substances. The purpose of this study was to determine the anti-inflammatory activity of papaya leaf water extract (Carica papaya L.) on the feet of male Wistar rats which were induced by carrageenan 1%. The research method used is experimental. The stages of this study include plant identification, making dry simplicia powder, simplicia characteristics, extracting papaya leaves using water, simplicia phytochemical screening and papaya leaf water extract (EADP), as well as testing for anti-inflammatory activity. Anti-inflammatory testing was carried out on 20 male Wistar rats induced with 1% carrageenan sub plantar. The test group was divided into five groups for the induction, comparison, EADP 50, 100, 200 mg/kg BW groups. The parameters observed were the volume of mouse leg udema measured by a pletismometer every 30 min for 5 h. Data obtained then calculated percent inflammation and percent inflammation inhibition. Furthermore, it was analysed by ANOVA with a confidence level of 95%. The results of the simplicia characteristics showed that the water content, water content of the sea water and soluble extracts of ethanol were 8.9%, 51.4% and 10.2% respectively. The results of simplicia and EADP phytochemical screening showed the content of flavonoids, tannins, triterpenoids, glycosides, and alkaloids. Observations of the percentage of inflammation in the induction group had the highest percentage of inflammation compared with the other test groups at time of 300 min (p 0.05). Whereas the percentage of inflammatory inhibition of all groups of test extracts has effectiveness comparable to the comparison group. EADP group 200 mg/kg BW is the best dose of extract as anti-inflammatory, where flavonoid compounds are thought to be responsible for decreasing the volume of inflammation in the legs of test animals.